Energy-saving and environmentally friendly high-transparent borate glass and preparation method thereof

By doping CeO2 and Cs2CO3 in highly transparent borate glass, the Ce3+/Ce4+ content and reducing atmosphere are regulated, and the problem of glass reflecting near-infrared light in summer and heat loss in winter is solved, and effective shielding of ultraviolet and near-infrared is achieved. Reduce building energy consumption and ultraviolet radiation damage, and is suitable for smart windows and other fields.

CN117185654BActive Publication Date: 2024-12-17HUBEI UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311018312.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-11
Publication Date
2024-12-17
Estimated Expiration
2043-08-11

AI Technical Summary

Technical Problem

Existing glass reflects near-infrared light in summer, causes high indoor temperatures, and causes heat loss in winter, increasing building energy consumption. At the same time, ultraviolet rays cause damage to human bodies and optoelectronic products. The existing technology is difficult to effectively block ultraviolet and infrared light.

Method used

Using Sr2.99-aB14O24:0.01Ce3+/4+, aCs+, highly transparent borate glass, through CeO2 and Cs2CO3 doping materials, the Ce3+/Ce4+ content ratio and reduction atmosphere are controlled, and the ultraviolet and near-infrared shielding performance is enhanced, and the UV and near-infrared shielding performance is enhanced. During the calcination process, reduce carbon is used to control the atmosphere and adjust the ultraviolet shielding range of the glass.

Benefits of technology

It realizes effective in reducing building energy consumption and UV radiation damage without affecting lighting, and provides ultraviolet and near-infrared shielding effects. It is suitable for smart windows and other fields that require thermal insulation and ultraviolet rays.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117185654B_ABST
    Figure CN117185654B_ABST
Patent Text Reader

Abstract

This application provides an energy-saving, environmentally friendly, and highly transparent borate glass and a preparation method thereof. The chemical general formula of the highly transparent borate glass is: Sr 2.99‑a B 14 O 24 : 0.01Ce 3+ / 4+ , aCs + ; wherein, 0 < a ≤ 0.04. The energy-saving, environmentally friendly, and highly transparent borate glass of this application has stronger ultraviolet shielding ability by doping ions Ce 3+ / 4+ . Its ultraviolet shielding region range is broadened by regulating the content ratio of Ce 3+ / Ce 4+ . It also has near-infrared shielding performance by co-doping Cs + . The energy-saving, environmentally friendly, and highly transparent borate glass of this application has ultraviolet and near-infrared shielding abilities, and at the same time has sunscreen and heat insulation effects, and can be used in daily life fields such as buildings and vehicles that require heat insulation and ultraviolet protection. The preparation method of an energy-saving, environmentally friendly, and highly transparent borate glass of this application regulates the degree of reducing atmosphere in the synthesis process by adjusting the amount of reducing carbon, thereby changing the concentration ratio of Ce 3+ / Ce 4+ to change the ultraviolet shielding region range of the transparent borate glass.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy-saving, environmentally friendly and multifunctional optical glass preparation, and more specifically, to a highly transparent borate glass with ultraviolet and infrared blocking properties and a preparation method thereof. The glass can be used in the field of smart windows for green buildings. Background Art

[0002] Sunlight is the most important natural light source. In addition to visible light radiation, near infrared and infrared light (780-2500nm) account for about 50% of the total radiation energy. In addition, ultraviolet light in the 220-400nm band accounts for about 5% of the total radiation energy of sunlight.

[0003] Near-infrared and infrared light with strong thermal effects are the main factors for the increase in ambient temperature. With the extensive use of glass exterior walls and curtain walls in cities, the phenomenon of high indoor temperatures in summer has become more prominent. On the contrary, infrared heat radiation from indoors to outdoors in winter will cause indoor heat loss and temperature drop. These have led to the extensive use of HVAC systems, and building energy consumption has continued to rise, accounting for 50% of the total social energy consumption. And due to the continuous use of HVAC systems, the energy saving ratio is usually less than 50%.

[0004] In addition, strong ultraviolet rays in summer have high photon energy, and excessive and long-term radiation will accelerate the aging and failure of optoelectronic products. Ultraviolet rays can also damage the human epidermis, leading to accelerated skin aging and serious skin diseases such as skin cancer.

[0005] Therefore, developing new glass energy-saving technologies that can effectively block ultraviolet and near-infrared light will greatly reduce building energy consumption and ultraviolet radiation damage, and rationally utilize the sun's light and heat, which has important scientific and practical significance for controlling building energy consumption and achieving green and low-carbon living. Summary of the invention

[0006] The purpose of the present application is to provide an energy-saving and environmentally friendly highly transparent borate glass and a preparation method thereof, so as to provide a highly transparent borate glass with ultraviolet isolation and infrared blocking functions, which can reduce ultraviolet radiation damage without affecting lighting, and more importantly, strengthen the management of indoor and outdoor infrared thermal radiation, and effectively reduce building energy consumption.

[0007] To achieve the above-mentioned purpose, the first aspect of the present application provides an energy-saving and environmentally friendly high-transparent borate glass, the chemical formula of which is: Sr 2.99-a B 14 O 24 :0.01Ce 3+ / 4+ , aCs + ; Among them, 0 <a≤0.04。

[0008] Furthermore, the matrix material of the highly transparent borate glass is Sr3B 14 O 24 , doping materials are CeO2, Cs2CO3. Sr3B 14 O 24 The matrix material has higher stability due to its highly polymerized double-layer structure. 14 O 24 The transmittance in the visible light region is as high as over 80%, while the transmittance in the ultraviolet region is lower, which can enhance the ultraviolet shielding performance.

[0009] Furthermore, the highly transparent borate glass is obtained by calcining a mixture of raw materials having a mass percentage of SrCO3: 30-35%, H3BO3: 65-70%, CeO2: 0.3-0.4%, and Cs2CO3: 0-1.5%.

[0010] Furthermore, the calcination is carried out in a reducing atmosphere, the calcination temperature is 900-1200° C., and the time is 4-5 hours.

[0011] Furthermore, the amount of H3BO3 weighed is excessive to compensate for the volatilization loss of the raw material H3BO3 at high temperature. Furthermore, the weight of H3BO3 weighed is increased by 10%.

[0012] Furthermore, the purity of each raw material in the mixed raw material is 99.99% analytical purity.

[0013] In a second aspect of the present application, a method for preparing energy-saving, environmentally friendly and highly transparent borate glass is provided, comprising the following steps:

[0014] According to the chemical formula Sr 2.99-a B 14 O 24 :0.01Ce 3+ / 4+ , aCs + Calculate and weigh the corresponding raw materials, add anhydrous ethanol to the weighed raw materials and grind them to obtain fully mixed raw materials;

[0015] In a reducing atmosphere, the fully mixed raw materials are heated to 900-1200° C. and kept warm for 4-5 hours. After cooling to room temperature, the sample is taken out for grinding and polishing to obtain the highly transparent borate glass.

[0016] Furthermore, the heating rate of the heating is 5-10°C / min.

[0017] Further, the reducing atmosphere is controlled by using reducing carbon during the calcination process.

[0018] Furthermore, the Ce in the highly transparent borate glass 3+ / Ce 4+ The content ratio of Ce in high transparent borate glass is controlled by reducing atmosphere of different degrees. 3+ / Ce 4+ The content ratio of the borate glass can be adjusted to adjust the ultraviolet shielding range of the high-transparency borate glass. Furthermore, the different degrees of reducing atmosphere can be controlled by adjusting the amount of reducing carbon.

[0019] Furthermore, the room temperature refers to 20±5°C.

[0020] Compared with the prior art, this application has the following technical effects:

[0021] The present invention relates to an energy-saving, environmentally friendly, highly transparent borate glass Sr 2.99-a B 14 O 24 :0.01Ce 3+ / 4+ , aCs + By doping Ce ions 3+ / 4+ It has stronger UV shielding ability, by regulating Ce 3+ / Ce 4+ The content ratio of Cs + It also has near-infrared shielding performance. 2.99-a B 14 O 24 :0.01Ce 3+ / 4+ It can shield ultraviolet and near-infrared without affecting the excellent lighting performance, and has sun protection and heat insulation effects. It can be used in daily life areas such as buildings and vehicles that require heat insulation and ultraviolet protection. It is an ideal material for smart windows.

[0022] The present invention relates to an energy-saving, environmentally friendly, highly transparent borate glass Sr 2.99-a B 14 O 24 :0.01Ce 3+ / 4+ , aCs + It has a very high transmittance in the visible light region. Compared with the currently available UV and infrared shielding coatings, it has irreplaceable advantages such as easy use, simpler process and higher thermal stability.

[0023] The present invention discloses a method for preparing energy-saving, environmentally friendly and highly transparent borate glass, which adjusts the amount of reducing carbon used to control the degree of reducing atmosphere during the synthesis process, thereby changing the Ce 3+ / Ce 4+ The concentration ratio is adjusted to change the UV shielding range of the transparent borate glass. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0025] Figure 1 Sr3B provided in the embodiment of the present application 14 O 24 Absorption spectra of the glass matrix and the energy-saving, environmentally friendly, highly transparent borate glass of Examples 1-3;

[0026] Figure 2 Sr3B provided in the embodiment of the present application 14 O 24 Transmission spectra of the glass matrix and the energy-saving, environmentally friendly, highly transparent borate glass of Examples 1-3;

[0027] Figure 3 This is an X-ray photoelectron spectrum (XPS) diagram of the energy-saving, environmentally friendly and highly transparent borate glass provided in Example 4 of the present application;

[0028] Figure 4 Absorption spectra of energy-saving, environmentally friendly and highly transparent borate glass provided in Examples 3-6 of the present application;

[0029] Figure 5 This is a transmission spectrum of the energy-saving, environmentally friendly and highly transparent borate glass provided in Examples 3-6 of the present application. DETAILED DESCRIPTION

[0030] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0031] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0032] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0033] S3B 14 O 24 Glass Matrix:

[0034] Synthesis process: Calculate and weigh the raw materials: 0.8858g SrCO3, 1.9045g H3BO3. In order to make the raw materials fully react, they need to be mixed evenly first, that is, add anhydrous ethanol to the agate mortar for grinding. After the anhydrous ethanol is completely volatilized, the mixed raw materials are first placed in an alumina crucible, and then placed in a KF1700 box muffle furnace for calcination in air. The temperature is raised to 900℃ at a rate of 5℃ / min, and then kept warm for 4h. After cooling to room temperature, the sample is taken out and polished to obtain Sr3B 14 O 24 Glass matrix.

[0035] Example 1: Sr 2.99 B 14 O 24 :0.01Ce 3+ / 4+ Glass sample, no reducing carbon.

[0036] Synthesis process: Calculate and weigh the raw materials: 0.8769g SrCO3, 1.9045g H3BO3, 0.0103gCeO2. In order to make the raw materials fully react, they need to be mixed evenly, that is, add anhydrous ethanol to the agate mortar for grinding. After the anhydrous ethanol is completely volatilized, the mixed raw materials are first placed in an alumina crucible, and then placed in a KF1700 box muffle furnace for calcination in air. The temperature is raised to 900℃ at a rate of 5℃ / min, and then kept warm for 4h. After cooling to room temperature, the sample is taken out for polishing.

[0037] In this embodiment 1, since the Ce source is CeO2 and is synthesized under a non-reducing atmosphere, the Sr 2.99 B 14 O 24 :0.01Ce 3+ / 4+ Ce in glass samples 4+ High concentration, contains only trace amounts of Ce 3+ .

[0038] The absorption spectrum of the glass sample obtained in this Example 1 is as follows Figure 1As shown, compared with Sr3B 14 O 24 The matrix glass has a characteristic absorption of longer wavelength ultraviolet light.

[0039] The transmittance of the glass sample obtained in Example 1 was tested. Figure 2 It is shown that the transmittance in the visible light region is as high as about 80%, but compared with Sr3B 14 O 24 The transmittance of the matrix glass, Example 1, drops to almost zero in the ultraviolet region with a longer wavelength.

[0040] The absorption line spectrum and transmittance line spectrum of the glass sample obtained in Example 1 both show that Ce-doped 3+ / 4+ Can enhance Sr3B 14 O 24 The ultraviolet shielding performance of the matrix glass widens the shielding range while still maintaining high transparency.

[0041] Example 2: Sr 2.99 B 14 O 24 :0.01Ce 3+ / 4+ Glass sample, small amount 0.1377g of reduced carbon.

[0042] The synthesis process is different from that of Example 1 in that Example 2 is calcined in a muffle furnace containing a small amount of reducing carbon, i.e., 0.1377 g of reducing carbon is placed in the furnace, and a reducing atmosphere is created by placing reducing carbon in the furnace.

[0043] Since Example 2 was synthesized in a reducing atmosphere containing a small amount of 0.1377 g of reducing carbon, the Ce in Example 2 3+ The concentration of will increase to a certain extent compared with Example 1.

[0044] The absorption spectrum of the glass sample obtained in Example 2 is as follows: Figure 1 As shown, its characteristic absorption of ultraviolet light is located at a higher level than Sr3B 14 O 24 The matrix glass absorbs at longer wavelengths but absorbs at shorter wavelengths than Example 1.

[0045] The transmittance of the glass sample obtained in Example 2 was tested. Figure 2 As shown in FIG. 1 , the transmittance is still high in the visible light range, but compared with Example 1, the transmittance of Example 2 drops to almost 0 in the shorter wavelength ultraviolet region.

[0046] Compared with Example 1, the absorption line spectrum and transmittance line spectrum of the glass sample obtained in Example 2 can be used to adjust the Ce 3+ / Ce 4+The content ratio can also change the range of UV shielding, but will not affect the transmittance.

[0047] Example 3: Sr 2.99 B 14 O 24 :0.01Ce 3+ / 4+ Glass sample, excess 0.3805 g reduced carbon.

[0048] The synthesis process is different from that of Example 1 in that Example 3 is calcined in a muffle furnace containing excess reducing carbon, i.e., 0.3805 g of reducing carbon is placed in the furnace, and a reducing atmosphere is created by placing reducing carbon in the furnace.

[0049] This Example 3 was synthesized under a reducing atmosphere containing an excess of 0.3805 g of reducing carbon, so Ce in Example 3 3+ The concentration of Ce in Example 1, Example 2 and Example 3 will increase to a greater extent. 3+ The content increases successively.

[0050] The absorption spectrum of the glass sample obtained in Example 3 is as follows: Figure 1 As shown, its characteristic absorption in the ultraviolet region is located at a 14 O 24 The matrix glass absorbs at longer wavelengths but absorbs at shorter wavelengths than Example 2.

[0051] The transmittance of the glass sample obtained in Example 3 was tested. Figure 2 As shown in FIG. 1 , the transmittance is still high in the visible light range, but compared with Example 2, the transmittance of Example 3 drops to almost 0 in the shorter wavelength ultraviolet region.

[0052] Compared with the absorption line spectrum and transmittance line spectrum of the glass sample obtained in Example 3, the increase of Ce 3+ / Ce 4+ The concentration ratio can move the UV shielding area toward the shorter wavelength direction, but will not affect the transmittance.

[0053] The comparison of the absorption line spectrum and transmittance line spectrum of the glass sample obtained in Example 3 with those in Example 1 and Example 2 shows that the reasonable regulation of Ce 3+ / Ce 4+ The concentration ratio makes it possible to achieve UV shielding covering the entire UV region.

[0054] Example 4: Sr 2.99 B 14 O 24 :0.01Ce 3+ / 4+ , 0.01Cs +Glass sample, excess 0.3805 g reduced carbon.

[0055] The synthesis process is different from that of Example 3 in that the raw materials weighed in Example 4 are: 0.8681 g SrCO3, 1.9045 g H3BO3, 0.0103 g CeO2, and 0.0098 g Cs2CO3.

[0056] This embodiment 4 is based on the embodiment 3 and co-doped with 1% Cs + .

[0057] The XPS spectrum of the glass sample obtained in this Example 4 is as follows: Figure 3 This confirms the successful incorporation of Ce and Cs ions of two valence states into the sample.

[0058] The absorption spectrum of the glass sample obtained in Example 4 is as follows: Figure 4 As shown, its characteristic absorption in the ultraviolet region has not changed significantly compared with Example 3, but has a higher absorption value in the near-infrared region (800-1700nm) than Example 3.

[0059] The transmittance of the glass sample obtained in Example 4 was tested. Figure 5 It is shown in the figure that the transmittance is still very high in the visible light range, and its transmittance in the ultraviolet region is still 0 compared to Example 3, but the transmittance in the near-infrared region (800-1700nm) is reduced.

[0060] The absorption line spectrum and transmittance line spectrum of the glass sample obtained in Example 4 compared with those in Example 3 can illustrate that 1% Cs + The doping has no effect on the transmittance in the visible light region and the shielding ability in the ultraviolet region, but enhances the infrared shielding ability.

[0061] Example 5: Sr 2.99 B 14 O 24 :0.01Ce 3+ / 4+ , 0.02Cs + Glass sample, excess 0.3805 g reduced carbon.

[0062] The synthesis process is different from that of Example 3 in that the raw materials weighed in Example 5 are: 0.8592 g SrCO3, 1.9045 g H3BO3, 0.0103 g CeO2, and 0.0196 g Cs2CO3.

[0063] This embodiment 4 is based on the embodiment 3 and co-doped with 2% Cs + .

[0064] The absorption spectrum of the glass sample obtained in this Example 5 is as follows: Figure 4As shown, its characteristic absorption in the ultraviolet region has not changed significantly compared with Example 3 and Example 4, but has a higher absorption value in the near-infrared region (800-1700nm) than both Example 3 and Example 4.

[0065] The transmittance of the glass sample obtained in Example 5 was tested. Figure 5 It is shown that the transmittance in the visible light range is still very high, and its transmittance in the ultraviolet region is still 0 compared to Example 3 and Example 4, but the transmittance in the near-infrared region (800-1700nm) is reduced.

[0066] The absorption line spectrum and transmittance line spectrum of the glass sample obtained in Example 5 compared with those in Example 3 and Example 4 can illustrate that 2% Cs + The doping has no effect on the transmittance in the visible light region and the shielding ability in the ultraviolet region, but enhances the infrared shielding ability.

[0067] Example 6: Sr 2.99 B 14 O 24 :0.01Ce 3+ / 4+ , 0.03Cs + Glass sample, excess 0.3805 g reduced carbon.

[0068] The synthesis process is different from that of Example 3 in that the raw materials weighed in Example 6 are: 0.8503 g SrCO3, 1.9045 g H3BO3, 0.0103 g CeO2, and 0.0293 g Cs2CO3.

[0069] This embodiment 6 is based on the embodiment 3 and co-doped with 3% Cs + .

[0070] The absorption spectrum of the glass sample obtained in Example 6 is as follows: Figure 4 As shown, its characteristic absorption in the ultraviolet region has not changed significantly compared with Example 3, Example 4 and Example 5, but has an absorption value in the near-infrared region (800-1700nm) that is higher than Example 3 but lower than Example 4 and Example 5.

[0071] The transmittance of the glass sample obtained in Example 6 was tested. Figure 5 It is shown that the transmittance in the visible light range is still very high, and its transmittance in the ultraviolet region is still 0 compared to Example 3, Example 4 and Example 5, but the transmittance in the near-infrared region (800-1700nm) is improved compared to Example 3, but reduced compared to Example 4 and Example 5.

[0072] The absorption line spectrum and transmittance line spectrum of the glass sample obtained in Example 6 compared with those in Examples 3, 4 and 5 can illustrate that 3% Cs + The doping has no effect on the transmittance in the visible light region and the shielding ability in the ultraviolet region, but the infrared shielding ability is enhanced compared with Example 3, but is reduced compared with Examples 4 and 5.

[0073] The present application embodiment provides a co-doped Ce 3+ / 4+ and Cs + Highly transparent borate glass Sr with both UV and infrared shielding capabilities 2.99-a B 14 O 24 :0.01Ce 3+ / 4+ , aCs + .

[0074] The embodiment of the present application provides a method for adjusting the degree of reducing atmosphere in the synthesis process by adjusting the amount of reducing carbon, thereby changing the Ce 3+ / Ce 4+ concentration ratio method, by doping Ce 3+ / 4+ Enhanced Sr3B 14 O 24 The inherent UV shielding ability of glass and the regulation of Ce 3+ / Ce 4+ A method of changing the shielding range by adjusting the concentration ratio.

[0075] The energy-saving, environmentally friendly and highly transparent borate glass Sr 2.99-a B 14 O 24 :0.01Ce 3+ / 4+ , aCs + By doping Ce ions 3+ / 4+ It has stronger UV shielding ability, by regulating Ce 3+ / Ce 4+ The content ratio of Cs + It also has near-infrared shielding performance. 2.99-a B 14 O 24 :0.01Ce 3+ / 4+ It has UV and near-infrared shielding capabilities, and also has sun protection and heat insulation effects. It can be used in daily life areas such as buildings and vehicles that require heat insulation and UV protection.

[0076] The method for preparing energy-saving, environmentally friendly and highly transparent borate glass in the embodiment of the present application adjusts the amount of reducing carbon used to control the degree of reducing atmosphere during the synthesis process, thereby changing Ce 3+ / Ce 4+ The concentration ratio is adjusted to change the UV shielding range of the transparent borate glass.

[0077] The energy-saving, environmentally friendly and highly transparent borate glass Sr 2.99-a B 14 O 24 :0.01Ce 3+ / 4+ , aCs + It has a very high transmittance in the visible light region. Compared with the currently available UV and infrared shielding coatings, it has irreplaceable advantages such as easy use, simpler process and higher thermal stability.

[0078] The above embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several modifications and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. An energy-saving, environmentally friendly and highly transparent borate glass. It is characterized in that The chemical general formula of the highly transparent borate glass is: Sr 2.99-a B 14 O 24 : 0.01Ce 3+ / 4+ , aCs + ; wherein, 0 < a ≤ 0.04, the matrix material of the highly transparent borate glass is Sr 3 B 14 O 24 , the doping materials are CeO 2 , Cs 2 CO 3 , the trivalent and tetravalent states of element Ce coexist, and the ultraviolet shielding region range is broadened by regulating the content ratio of Ce 3+ / Ce 4+ .

2. The energy-saving, environmentally friendly and highly transparent borate glass as claimed in claim 1, It is characterized in that The highly transparent borate glass is composed of SrCO 3 :30-35%, H 3 BO 3 :65-70%, CeO 2 :0.3-0.4%, Cs 2 CO 3 : 0-1.5% of the mixed raw materials are calcined, and the total mass of the above raw materials is 100%.

3. The energy-saving, environmentally friendly and highly transparent borate glass as claimed in claim 2, It is characterized in that The calcination is carried out in a reducing atmosphere, the calcination temperature is 900-1200° C., and the calcination time is 4-5 h.

4. The energy-saving, environmentally friendly and highly transparent borate glass as claimed in claim 3, It is characterized in that The H 3 BO 3 The amount weighed is excessive.

5. The energy-saving, environmentally friendly and highly transparent borate glass as claimed in claim 3, It is characterized in that The purity of each raw material in the mixed raw material is 99.99% analytical purity.

6. A method for preparing energy-saving, environmentally friendly and highly transparent borate glass according to any one of claims 1 to 5, It is characterized in that The following steps are involved: According to the chemical formula Sr 2.99-a B 14 O 24 :0.01Ce 3+ / 4+ , aCs + Calculate and weigh the corresponding raw materials, add anhydrous ethanol to the weighed raw materials and grind them to obtain fully mixed raw materials; In a reducing atmosphere, the fully mixed raw materials are heated to 900-1200° C. and kept warm for 4-5 hours. After cooling to room temperature, the sample is taken out and polished to obtain the highly transparent borate glass.

7. A method for preparing energy-saving, environmentally friendly and highly transparent borate glass as claimed in claim 6, It is characterized in that The heating rate of the heating is 5-10°C / min.

8. A method for preparing energy-saving, environmentally friendly and highly transparent borate glass as claimed in claim 6, It is characterized in that The reducing atmosphere is controlled by using reducing carbon during the calcination process.

9. A method for preparing energy-saving, environmentally friendly and highly transparent borate glass as claimed in claim 8, It is characterized in that The Ce in the highly transparent borate glass 3+ / Ce 4+ The content ratio is controlled by reducing the atmosphere to varying degrees.

Citation Information

Patent Citations

  • Rare earth doped multicolor fluorescence emission borate glass and preparation method thereof

    CN117185656A